A new family of decanuclear Ln7Cr3 clusters exhibiting a magnetocaloric effect. Issue 28 (12th May 2021) - Yin, Jia-Jia; Lu, Tian-Qi; Chen, Cheng; Shi, Hai-Yan; Zhuang, Gui-Lin; Zheng, Jun; Fang, Xiaolong; Zheng, Xiu-Ying
Abstract : Two decanuclear Ln–Cr clusters Ln7 Cr3 were obtained, which formed a three-dimensional framework with one-dimensional nanopore channel through hydrogen-bond and π-bond interactions. Gd7 Cr3 had a magnetic entropy change of 21.1 J kg −1 K −1 at 5 K, 7 T. Abstract : Two dimeric Ln–Cr clusters with formula {Ln(H2 O)8 [Ln6 Cr3 (L)6 (CH3 COO)6 (μ3 -OH)12 (H2 O)12 ]}·(ClO4 )6 · x H2 O (Ln = Gd, x = 35 for 1 and Ln = Dy, x = 45 for 2, HL = 2-pyrazinecarboxylic acid) were obtained by a ligand-controlled hydrolytic method with a mixed ligand system (2-pyrazinecarboxylic acid and acetate). Single crystal structure analysis showed that two trigonal bipyramids of [Gd3 Cr2 (μ3 -OH)6 ] 9+ worked as building blocks in constructing the metal-oxo cluster core of [Gd6 Cr3 (μ3 -OH)12 ] 15+ by sharing a common top – a Cr 3+ ion. Additionally, compound 1 forms a three-dimensional framework with a one-dimensional nanopore channel along the a -axis through a hydrogen-bond interaction between the cationic cluster core and the free mononuclear cation [Gd(H2 O)8 ] 3+ and the π-bond interactions of the pyrazine groups on the two cationic cluster cores. Magnetic calculations indicated a weak ferromagnetic coupling interaction for Gd⋯Gd and Gd⋯Cr in compound 1, with its magnetic entropy change (−Δ S m ) reaching 21.1 J kg −1 K −1 at 5 K, 7 T, while compound 2 displayed an obvious frequency-dependency at H dc = 2000 Oe.